Immersive Record and Replay for Lively Virtual Environments - Brandstatter, Klara (2023 IEEE Conference on Virtual Reality and 3D User Interfaces Abstracts and Workshops (VRW), 2023)
Non-player characters (NPCs) play an important role in virtual en-vironments and make them more lively. I am using recording and replaying techniques in virtual reality which enable a single user to interact with previous recordings of themselves. I conducted a user study that suggested that recordings that are performed by a single user are indistinguishable from multi-user recordings. En-couraged by these results, I would like to use machine learning to improve the existing recording and replaying techniques to create more sophisticated NPCs that can react to the user.